2019
DOI: 10.1038/s41598-019-44852-6
|View full text |Cite|
|
Sign up to set email alerts
|

Visual Field Prediction using Recurrent Neural Network

Abstract: Artificial intelligence capabilities have, recently, greatly improved. In the past few years, one of the deep learning algorithms, the recurrent neural network (RNN), has shown an outstanding ability in sequence labeling and prediction tasks for sequential data. We built a reliable visual field prediction algorithm using RNN and evaluated its performance in comparison with the conventional pointwise ordinary linear regression (OLR) method. A total of 1,408 eyes were used as a training dataset and another datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 30 publications
0
54
0
2
Order By: Relevance
“…Many articles compared deep learning with state‐of‐the‐art models on various datasets and achieved a robust performance 35–42 . It has been shown that deep learning are not only effective in fundus photographs for the diagnosis of glaucoma but also in Optical Coherence Tomography 43–48 and visual fields 49–52 . AI has been showed effective in other ophthalmic diseases, like age‐related macular degeneration and diabetic retinopathy 9,53 .…”
Section: Discussionmentioning
confidence: 99%
“…Many articles compared deep learning with state‐of‐the‐art models on various datasets and achieved a robust performance 35–42 . It has been shown that deep learning are not only effective in fundus photographs for the diagnosis of glaucoma but also in Optical Coherence Tomography 43–48 and visual fields 49–52 . AI has been showed effective in other ophthalmic diseases, like age‐related macular degeneration and diabetic retinopathy 9,53 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that at four years of followup, the model identified 35% of the eyes as progressing versus only 15% for MD. In another study, Park et al 90 used a recurrent neural network and showed that it achieved better prediction of future visual field observations compared to ordinary least squares linear regression. Wen et al 91 also attempted to set up a deep learning model to predict future visual field observations based on the first visual field test only.…”
Section: Glaucoma Progressionmentioning
confidence: 99%
“…RNN is a good network for extracting information features related to dynamic systems at the hidden layer [10]. Recurrent Neural Network have been used for prediction in several studies [11], [12]. The difference of RNN with NN lies in the value of the input not only from outside the network but added from the hidden layer output value.…”
Section: Recurrent Neural Networkmentioning
confidence: 99%